Implementing Lexical Choice Strategies for Writing Short Descriptive Texts at Pondok An Nahdloh, Selangor, Malaysia - Mujad Didien Afandi; Savira Zaniar; Nailul Authar; Novi Rahmania Aquariza; Edi Pujo Basuki; Destita Shari (UKInstitute, 2026)
Limited vocabulary and inappropriate word selection often hinder junior high school students from producing effective English descriptive texts. To address this issue, a community service program entitled Teaching Lexical Choice for Writing Short Descriptive Texts at Pondok An Nahdloh, Selangor, Malaysia was conducted to improve students’ lexical diversity, lexical appropriateness, and linguistic development. The program involved fifteen Indonesian junior high school students and was implemented through a participatory training approach consisting of preparation, implementation, and evaluation stages. Instructional activities included introducing lexical choice, practicing synonym use, selecting contextually appropriate vocabulary, and writing short self-descriptive texts. Students completed writing tasks before and after the training, and their texts were evaluated using a lexical analysis rubric covering lexical diversity, lexical appropriateness, lexical density, register awareness, and overall lexical control. The findings showed substantial improvement in students’ lexical performance. The average total score increased from 12.07 (Fair) in the pre-writing task to 21.80 (Excellent) in the post-writing task. Students demonstrated greater vocabulary variation, more precise word selection, higher lexical density, and improved control of descriptive language. These findings indicate that lexical-choice instruction is an effective strategy for enhancing students’ writing quality and supporting linguistic development in English language learning.